Mitochondrial genome of a brachypterous species in Meconematinae: Acosmetura nigrogeniculata and its phylogenetic implication - Ning Han; Hao Yuan; Jing Wang; Yafu Zhou; Shaoli Mao (Mitochondrial DNA. Part B. Resources, 2019)
Acosmetura nigrogeniculata (Liu and Wang, ) is a brachypterous species in Meconematinae, which is only distributed in China. In this study, the complete mitochondrial genome of A. nigrogeniculata was determined and annotated. The 16,271 bp circular genome contained 13 protein-coding genes, 22 transfer RNA genes, two ribosomal RNA genes, and one control region. The overall base composition was 36.4% A, 34.8% T, 18.4% C, and 10.5% G, exhibiting obvious anti-G and AT bias (71.2%). The general genomic characters including nucleotides composition, gene arrangement, and codon usage were similar to those of other Meconematinae species. Phylogenetic analysis of all nine Meconematinae species indicated that the newly sequenced species were clustered closely with the brachypterous species Pseudosmetura snjiensis.